Treatment with Buttress Plate Technique for Symptomatic Ulnar Styloid Base Nonunion - Kümbüloğlu, Ömer Faruk; Cam, Necmi; Özdemir, Hacı Mustafa (Journal of Wrist Surgery, 2021)
Background Surgical treatment options for symptomatic ulnar styloid base nonunion can be divided into two groups: styloid excision and styloid fixation methods. Styloid fixation is commonly performed using tension band wiring or distal ulna hook plate. However, these methods are more suitable for large styloids than small ones. For this reason, fixation of small styloids still remains a problem.Purpose To present the surgical details and results of patients operated using the buttress plate technique, due to the symptomatic ulnar styloid base nonunion.Patients and Methods In this study, 11 patients who underwent surgery for symptomatic ulnar styloid base nonunion using buttress plate technique were evaluated retrospectively. The patients were evaluated with the help of forearm and wrist range of motion, grip strength, disabilities of the arm, shoulder, and hand (DASH) score and visual analogue pain score.Results The mean follow-up period was 15 months (range: 13–21 months). Union was achieved in 10 patients. At the final follow-up, the forearm supination and pronation active range of motions were significantly higher than those in the preoperative period, the visual analogue pain score mean value was 0.7 (range: 0–5), and the DASH score mean value was 7 (range: 1–32).Conclusion We conclude that good results can be achieved with the buttress plate technique in patients with both large and small fragmented ulnar styloid base nonunions and no distal radioulnar joint instability.Level of Evidence This is a Level IV, therapeutic study.
Keywords: ulnar styloid nonunion; ulnar styloid fracture; ulnar-sided wrist pain; buttress plate; distal radioulnar joint instability